The Bunyaviridae - Kramer, Laura D. (Henry Stewart Talks, 2010)
Bunyaviridae family: basic biology, classification, vector and disease associations, viral structure, basic replication strategy, Specific arthropod-borne genera in the Bunyaviridae family, i.e. Bunyavirus, Phlebovirus, Nairovirus: transmission cycles and prevalence
Archived at 2021/08/29